Quality of life, anxiety, depression and hopelessness in infertile couples (Research, Society and Development, 2022)
Objectives: Evaluate quality of life, anxiety, depression and hopelessness of couples undergoing assessment/treatment at the public Human Reproduction Service in Brazil. Methods: All couples that were under assessment and treatment for fertilization from September 2014 to July 2015 were interviewed. The instruments used were the Hospital Anxiety and Depression Scale, the Fertility Quality of Life tool and Beck's Hopelessness Scale. Results: 272 people participated in this study (57.4% female). Symptoms of anxiety were found in 20.9%, of depression in 12.2% and hopelessness in 18.4% of the group. The results showed that the low indexes in the Emotional and Mind/Body subscales were related to depression symptoms in women, while in men the relationship with depression centered on the Mind/Body subscale. In the women, low indexes were found in the Emotional and Mind/Body subscales related to hopelessness, while in men the Mind/Body and Tolerability subscales were the most significantly compromised. Conclusions: The couple's experience becomes a greater risk of damage to quality of life during treatment, which furthers the possibility of significant impact to the physical and mental health of the couple.